ANALISIS CHASSIS PROTOTIPE GREEN AGV MENGGUNAKAN METODE FINITE ELEMENT ANALYSIS (FEA) DI AKADEMI KOMUNITAS TOYOTA INDONESIA - Suryawhan Arifandi; Muhammad Naufal Faqih; Harki Apriyanto (Jurnal Pendidikan Vokasi Otomotif, 2026)
Abstract The worsening impact of global warming is largely driven by excessive greenhouse gas carbon footprints. In 2022, Toyota reported a carbon footprint of 77,796 tons. To support environmental preservation campaigns, companies must take concrete steps to reduce emissions, one of which is through the "Plant Zero Emission Carbon" strategy. This study explores the development of a laboratory-scale prototype of a green Automated Guided Vehicle (AGV), utilizing SUS GF chassis material, hydrogen fuel cell power supply, and autonomous control systems. The research focuses on the first stage: designing and constructing the AGV chassis prototype, analyzing power consumption of the DC PG45 motor, and implementing mecanum wheels for towing-type AGV. Static testing using the Finite Element Analysis (FEA) method revealed a von Mises stress value of 7.75 MPa under a 21 kg load, which is well below the material's yield strength of 275 MPa, indicating structural safety. A second test was conducted at the critical point of the chassis, specifically at the DC PG45 motor bracket, assuming evenly distributed load across four brackets. The von Mises stress value obtained was 25.30 MPa under a 40 kg load, which also falls within the safe range. These results demonstrate that the SUS GF chassis design is feasible for the development of environmentally friendly AGVs.